The Importance of Adopting and Adapting Non-Conviction Based Asset Forfeiture Norms in Eradicating Corruption - Setyawan, Vincentius (Hikamatzu | Journal of Multidisciplinary, 2024)
Overcoming corruption in Indonesia, which is always growing very massively and has become entrenched, certainly requires an effective strategy. Pursuing corruptors and criminalizing them is not a good idea to eradicate corruption. Considering the trend of low sentences for corruptors in Indonesia, this does not have a deterrent effect at all. Non-Conviction Based Asset Forfeiture could be the answer to the difficulty of eradicating corruption due to the fact that it is not easy to prove corrupt actions. Focusing on assets is more important than criminalizing perpetrators. This article will discuss the urgency of adopting and adapting Non-Conviction Based Asset Forfeiture norms in eradicating corruption. This research uses normative legal research methods with a conceptual approach. The result of this research is that the implementation of the Non-Conviction Asset Forfeiture in Indonesia, apart from being implemented based on the Corruption Eradication Law, the State Attorney must be able to prove that there has been real state financial loss, the state financial loss was caused by criminal acts of corruption and there is a guarantee from the corruptor. to facilitate the implementation of confiscation of assets resulting from corruption without punishment.